Lipschitz regularity for solutions of the parabolic p-Laplacian in the Heisenberg group - Capogna, Luca; Citti, Giovanna; Zhong, Xiao (Annales Fennici Mathematici, 2023)
We prove local Lipschitz regularity for weak solutions to a class of degenerate parabolic PDEs modeled on the parabolic \(p\)-Laplacian \(_t u= _i=1^2n X_i (| abla_0 u|^p-2 X_i u),\) in a cylinder \(Ω×R^+\), where \(Ω\) is domain in the Heisenberg group \(H^n\), and \(2p 4\). The result continues to hold in the more general setting of contact subRiemannian manifolds.